CAFF Progress Report: April 2005 - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2005)
Arctic Council CAFF Working Group Progress Report Presented to the Senior Arctic Officials in Yakutsk, Russian Federation on 6-7 April 2005